State of the art of community-driven software engineering ontology evolution - Wongthongtham, Pornpit; Dillon, Tharam; Chang, Elizabeth (IEEE Computer Society, 2011)
Ontology evolution becomes an interesting topic in the semantic web field and increasingly getting research momentum. However, there is still a lack of understanding and support in ontology evolution. In this paper, we focus on an approach for ontology evolution of Software Engineering Ontology (SE Ontology) in multi-site software development setting. An integration of agents with semantic web technology and recommender systems to address communication and coordination issues is proposed together with a use of social networks for the purpose of ontology evolution.